Multidisciplinary dataset for geological and environmental studies in the lake of Cavazzo (Southern Alps) - Polonia, Alina; Albertazzi, Sonia; Bellucci, Luca Giorgio; Bonetti, Carla; Bonetti, Jarbas; Gallerani, Andrea; Giorgetti, Giulia; Giuliani, Silvia; López Correa, Matthias; Mayr, Christoph; Miserocchi, Stefano; Peruzza, Laura; et al. (Data in Brief, 2021)
The present dataset was collected to evaluate the environmental stressors on a lacustrine basin in the Eastern Alps of glacial origin that has been affected in recent years by natural and anthropogenic events such as the construction of a hydroelectric power plant and a series of strong earthquakes during 1976-1977. We collected sediment cores in different sites from the lake margins to the depocenter and performed a multiproxy analysis of sediment sample to highlight lake stratigraphy and major changes occurring at a decadal scale (Polonia et al., [1]). The integrated analyses of sedimentological, geochemical, isotopic, mineralogical and micropaleontological analyses aimed at reconstructing changes in sediment composition and define the triggering mechanisms of altered environmental conditions. The dataset demonstrates that evaluating ex post the effects of artificial modification in a natural environment during relatively long time spans (decades) can provide important insights for managing and protection strategies in similar environments worldwide
CRIS-Team Scopus Importer:2021-07-02
Keywords: Anthropogenic impacts; Earthquakes; Hydroelectric power plant; Lacustrine seismo-turbidite; Seismic hazard